Computers and data processing today : with BASIC. - Mandell, Steven L. (West Publishing Co., 1983)
"Two years of hard work with my publisher have resulted in the book you hold in your hand -Computers and Data Processing Today. I believe that this book continues my philosophy of presenting the educational material in a logical, uncluttered manner, while including relevant real-world examples. Additionally, by virtue of its full-color format and extensive use of graphics, I believe this book is one of the most visually appealing introductory computer books yet published. The basic pedagogical format found in this book is designed to aid in the clear, straightforward presentation of the material. Each chapter begins with a brief introductory section that provides a logical link with a previus material. The chapter outline that follows permits the student to develop a frame of reference for the text material. this outline also provides a useful guide when preparing for exams. At the conclusion of the chapter material, there is a proint-by-point summary in sentence form followed by approximately ten review questions." (Copied from the preface).